PERAN TEKNOLOGI TELEKOMUNIKASI DALAM MENDORONG INOVASI JARINGAN PERBANKAN SYARIAH - Asri, Liza; Najiyah, Chindy Jihan; Lubis, Arif Hidayat; Nurbaiti (JURNAL EKONOMI PEMBANGUNAN, 2024)
The development of telecommunications technology in the last few decades has had a significant impact on various sectors, including the banking sector. One area undergoing major transformation is Islamic banking, where telecommunications technology plays an important role in driving network and service innovation. This article aims to explore the role of telecommunications technology in encouraging Islamic banking network innovation. By analyzing various aspects, from technology implementation to its impact on customer satisfaction, it is hoped that it can provide a clearer picture of how telecommunications technology contributes to the growth and sustainability of sharia banking in this digital era. This research concludes that overall, telecommunications technology plays a vital role in encouraging innovation in Islamic banking networks in Indonesia. By increasing operational efficiency, expanding access to services, and creating a better customer experience, Islamic banks can compete effectively in this digital era. For this reason, it is important for Islamic banks to continue to adapt to technological developments and meet market demands in order to provide the best service to the community